Drip irrigation affects soil bacteria primarily through available nitrogen and soil fungi mainly via available nutrients - Wang, Xiaojuan; Zhang, Yu; Wang, Tianle; Wang, Lei; Liu, Enke (Frontiers in Microbiology, 2024)
The issue of water scarcity is a global concern. Water-saving irrigation has long been a topic of interest among agricultural researchers. In this study, changes in soil microbial community structure and diversity under different periods of drip irrigation were analyzed using the Illumina HiSeq high-throughput sequencing platform and 16S rRNA gene sequence amplification. Six treatments were established based on varying drip irrigation amounts: maintaining the drip irrigation amount at 320 mm without any increase (CK), increasing by 72 mm during different growth stages: from the sowing stage to the jointing stage (J), from the jointing stage to the big trumpet stage (B), from the big trumpet stage to the tasseling stage (T), from the tasseling stage to the grain filling stage (G), and from the grain filling stage to the maturity stage (M). Compared to CK, the T treatment significantly increased the Chao index of soil bacteria by 2.95%. The main bacterial phyla included Proteobacteria, Acidobacteria, blastomonas, Actinobacteria, Chloromycetes, and Bacteroidetes, while ascomycetes, basidiomycetes, chytridomycetes, and mortieromycetes were the main fungal phyla across different periods of drip irrigation. Zoopagales, Amtridomyces, and Trichomyces were absent in the G, T, and M treatments, respectively. The content of soil-available potassium in the T treatment was higher than that in other treatments, whereas the content of soil-available nutrients in the B treatment was the lowest. Overall, the T treatment had the highest content of available nutrients. Redundancy analysis showed that available nitrogen was the main soil chemical property affecting soil bacterial community structure, while soil-available nutrients were the main soil chemical property affecting the fungal community structure. Thus, the T treatment was effective in enhancing soil microbial community structure and increasing soil-available nutrients.